Mindsponge-based reasoning of households' financial resilience during the COVID-19 crisis - Minh-Hoang Nguyen; Quy Van Khuc; Viet Phuong La; Tam-Tri Le; Quang-Loc Nguyen; Jin Ruining; Phuong-Tri Nguyen; Quan Hoang Vuong (Journal of Risk and Financial Management, 2022)
The COVID-19 crisis was remarkable because no global recession model could predict or provide early notice of when the coronavirus pandemic would happen and damage the global economy. Resilience to financial shocks is crucial for households as future crises like COVID-19 are inevitable. Therefore, the current study aims to examine the effects of financial literacy and accessibility to financial information on the financial resilience of Vietnamese households through the lens of an information-processing perspective. The Bayesian Mindsponge Framework (BMF) analytics was employed on a dataset of 839 samples for the investigation. We found that households of respondents with better financial knowledge and investment skills are less likely to be financially affected during the peak of the COVID-19 crisis, but the effect of investment skills is weakly reliable. Accessibility to financial information through informal sources (having a household member working in the financial sector) and formal sources (participating in a financial course) is positively associated with the respondents' financial knowledge and investment skills. This finding suggests that the spillover effect of financial knowledge and skills among residents exists, leading to better resilience toward financial shocks. However, if the financial information is inaccurate, it might lead to misinformation, false beliefs, and poor economic decisions on a large scale.
Keywords: 650; financial literacy; financial resilience; information accessibility; mindsponge theory; crisis